Gereja St. Mary The Virgin, Jalan Raja, Kuala Lumpur / [mikrofilem] - Aznida Salwa Raja Azmi; Hidayah Mat Daud; Norfarizah Othman; Hani Yuliati Mohd. Lasa; Mohd. Aryan Mohd. Anuar; Mohd. Mahza Mohd. Tahir; Mohd. Saifrol Syeikh Naimullah; Amir Astar Lukman, 1975- (Skudai : Universiti Teknologi Malaysia, 1997)
Kajian Lukisan Terukur (Jabatan Senibina) - Universiti Teknologi Malaysia, 1997